Sociology of Communication: Analysing Social Inequality and Community Integration in Limau Village, Banyuasin Regency - Banderas , Antoni; Firmansyah, Firmansyah; Adeoye, Moses Adeleke (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2024)
Social disparities between hamlets caused by economic differences, technology accessibility, and education levels have an impact on communication patterns and community interactions, where inequality in Access to information can strengthen social hierarchies, stereotypes, and social exclusion among community groups. This study aims to analyse the social gap between hamlets in community interaction through the sociology of communication perspective. The research method used is a qualitative approach with the type of phenomenology. Data collection techniques were participatory observation, in-depth interviews, and documentation studies. This research was conducted in Limau village, Sembawa District, Banyuasin Regency. The informants in this study were local village officials. The results show that social disparities, such as educational level differences, access to resources, and cultural traditions, create significant communication barriers. This leads to limited social interaction and the emergence of stereotypes and prejudices between Hamlet residents. However, there were also efforts by the community and local leaders to reduce these disparities through joint activities and intergroup dialogue. The study concludes that an in-depth understanding of the communication dynamics and social factors underlying the gaps can be the foundation for building more harmonious and inclusive interactions between hamlets. The results of this study make an important contribution to understanding the socio-cultural dynamics that occur in Limau Village with three culturally distinct hamlets. It recommends several approaches to reduce social inequality in Limau Village, including strengthening education programs and increasing community literacy to address the root of the problem, which is identified as a lack of understanding and knowledge.